Predictive value of Admission Serum Cortisol for Mechanical Ventilation in Community-Acquired Pneumonia: A Prospective Study - Islam, Md. Khairul; Alam, Zebunnesa Nasrin; Sharif, Md. Mohiuddin; Hossain, Fahima Sharmin; Hossain, Muhammad Shakhawat; Sweety, Kawser Akter; Kabir, Md Asadul; Ahmed, Minhaj Uddin (Journal of Medicine, 2026)
Background: Early identification of patients requiring mechanical ventilation (MV), either invasive or non-invasive, is critical to reduce morbidity and mortality in community-acquired pneumonia (CAP). Cortisol,a primary stress hormone, may serve as a prognostic marker in CAP. Objective: To evaluate the association between admission serum cortisol levels and the need for MV in patients with CAP. Methods: This prospective study enrolled 92 adults with CAP admitted to Dhaka Medical College Hospital over 12 months. Serum cortisol was measured at 9:00 AM on the first available morning after admission using ELISA.All participants were categorized into high cortisol (>23 mcg/dL) and normal cortisol (< 23 mcg/dL) groups. The primary outcome was the requirement for MV. Logistic regression and receiver operating characteristic (ROC) analysis were applied to assess predictive value. Results: Patients with high cortisol had a significantly greater need for MV compared with those with normal levels (31.8% vs 4.2%, p = 0.001). High cortisol independently predicted MV (OR = 10.7, 95% CI: 2.28–50.6, p = 0.030). ROC analysis showed good discriminative ability for cortisol (AUC = 0.831), while CURB-65 (AUC = 0.972) and CRP (AUC = 0.947) performed better. Conclusion: Admission serum cortisol is independently associated with the need for MV in CAP patients and provides additional prognostic information beyond conventional severity scores. Incorporating cortisol measurement into early assessment may improve risk stratification and help guide timely escalation of care, especially in resource-limited settings.